PERANCANGAN APLIKASI BERBASIS ANDROID UNTUK KOMUNITAS PENGGEMAR BURUNG KICAU - Dian Sano, Albert V; Muhammad, Bintang Fadhli; Mangare, Edward Kristian; Jason, Jeremy; Hidayah, Taufiq (Infotech: Journal of Technology Information, 2019)
Industry 4.0 is developing and industry 4.0 is the name of the latest automation and data exchange trends in manufacturing technology. This term covers physical-cyber systems, the internet for everything, cloud computing, and cognitive computing. Industry 4.0 produces "smart factories". Industry 4.0 can be seen from More than 50 percent or about 143 million people out of 262 million Indonesians have been connected to the internet throughout 2017, at least according to the latest report by the Indonesian Internet Service Providers Association. The problem in this research is not understanding the advantages and disadvantages of the birds owned and the level of extinction of birds owned. The purpose of this research is to design an Android-based application for the bird enthusiast community. Twitter is an android based forum for the bird lovers community. The application of Android technology to information about the activities of the birds chirping community is an application that serves to provide effective information for members of the chirping mania community at various events, competitions and buying and selling birds. In this application users can post photos of birds, bird trading transactions. see news and race schedule information and tips on bird care to be ready to compete. This application was built using Android Studio and uses Business Model Canvas (BMC) design methods, Use Cases, Activity Diagrams, and Mock-ups. The result can simplify the process of buying and selling birdsong, and makes it easier for community members to get information on various events related to birdsong.